Building Brand Identity and Digital Marketing for the MSME Coffee Shop Petro’s Coffee Relevant to Gen Z and Millennials in Dairi Sidikalang - Ester Petronella Tarigan; Yossie Rossanty; Dewi Nurmasari Pane (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Brand identity is a crucial factor in shaping consumer perceptions and product differentiation in competitive markets. This study investigates the effects of brand identity and digital marketing on visit intention and purchase decision among Generation Z and Millennial consumers at a local coffee SME (PETRO’S COFFEE) in Sidikalang, Indonesia, with electronic word of mouth (e-WOM) as a mediating variable. A quantitative explanatory approach was employed using purposive sampling, resulting in 117 valid respondents who had made purchases within the last six months. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that brand identity has a positive and significant effect on visit intention, while digital marketing significantly influences purchase decision both directly and indirectly through e-WOM. The mediating role of e-WOM indicates that online reviews and consumer-generated recommendations strengthen the effectiveness of digital marketing communication. The coefficient of determination values demonstrate moderate to strong predictive power of the proposed model. This study contributes to the branding and digital marketing literature by providing empirical evidence from local coffee SMEs in non-metropolitan areas. Practically, the findings offer strategic insights for SME owners to integrate strong brand identity with digital marketing initiatives to engage younger consumers more effectively